Role of Chaperone-Mediated Autophagy in Ageing Biology and Rejuvenation of Stem Cells - Vitale, Emanuela; Perveen, Sadia; Rossin, Daniela; Lo Iacono, Marco; Rastaldo, Raffaella; Giachino, Claudia (Frontiers in Cell and Developmental Biology, 2022)
What lies at the basis of the mechanisms that regulate the maintenance and self-renewal of pluripotent stem cells is still an open question. The control of stemness derives from a fine regulation between transcriptional and metabolic factors. In the last years, an emerging topic has concerned the involvement of Chaperone-Mediated Autophagy (CMA) as a key mechanism in stem cell pluripotency control acting as a bridge between epigenetic, transcriptional and differentiation regulation. This review aims to clarify this new and not yet well-explored horizon discussing the recent studies regarding the CMA impact on embryonic, mesenchymal, and haematopoietic stem cells. The review will discuss how CMA influences embryonic stem cell activity promoting self-renewal or differentiation, its involvement in maintaining haematopoietic stem cell function by increasing their functionality during the normal ageing process and its effects on mesenchymal stem cells, in which modulation of CMA regulates immunosuppressive and differentiation properties. Finally, the importance of these new discoveries and their relevance for regenerative medicine applications, from transplantation to cell rejuvenation, will be addressed.